Smart Lamp: Kendali dan Monitor Lampu Berbasis Internet Of Things (IoT) - Suhardi; Rahmi Hidayati; Irma Nirmala (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Generally, people control the house light manually. The problem is that sometimes people forget to turn off the lights when they go. It caused a waste of energy and increased the bills. The light can be automated controlled or controlled from far by the Internet of Things (IoT) technology. This research developed automated several room lights in a miniature house by a website. The system has been successfully implemented. The user can control and monitor the condition of house lights by a web application. The control and monitoring process can be carried out in two modes. First, manual mode by pressing the on/off button on the application. Second, automatic mode by setting the time for each room light according to the conditions required by the user.